Successful treatment of Subclavian artery thrombosis with gangrene of fingers- a case report - Hoque, Md Rezwanul; Husain, Sabrina; Alauddin, Md; Rahman, Zerzina (University Heart Journal, 2009)
Mr. X, a smoker, normotensive, nondiabetic male patient of 24 years of age, presented with acute severe pain of the left upper extremity for 2 days. He had discoloration of the thumb and index finger for which he consulted a quack doctor who made an incision over the blackened area to drain subcutaneous collection and gave antibiotic and analgesics. There was no bleeding from the site of incision and regular dressing could not improve his condition. After waiting for 15 days without any improvement, he reported to a private clinic in Dhaka. Thorough physical examination and investigation revealed subclavian artery thrombosis due to cervical rib. The thoracic outlet syndrome was relieved by sclaneous muscle division and excision of the cervical rib, subclavian artery thrombectomy was possible through transbrachial route even after more than 2 weeks. doi: 10.3329/uhj.v5i1.3443 University Heart Journal Vol. 5, No. 1, January 2009 44-46